Factors influence the level of job satisfaction among registered nurses :a case study in Sarawak General Hospital, Kuching - Teng,, Mei Sin. (Universiti Malaysia Sarawak, UNIMAS, 2010)
The aim of this study is to identify factors that i nfluence the level of job satisfaction among registered nurses in general hospital. The fa ctors concerned are career advancement, compensation and benefits, organizatio nal commitment and work-life balance. Besides, this study also aims to investiga te the dominant factor that influences the level of job satisfaction among regi stered nurses. A quantitative survey approach by using questionnaires had been ca rried out as instrument for data collection. 120 sets of questionnaires were distrib uted to the registered nurses at Sarawak General Hospital. However, only 85 sets of valid questionnaires were being returned and used for the analysis. Pearson Correla tion “r” had been used to identify the relationship between the variables while Multip le Regression Linear was used to identify dominant factor that influences the level of job satisfaction among the registered nurses. The findings revealed that the l evel of job satisfaction among the registered nurses is in the average level and there are significant relationships between the independent variables and the dependent variable. Furthermore, career advancement is identified as the dominant factor th at influences the level of job satisfaction among the registered nurses. Thus, it is recommended that the management of the hospital should listen to the nee ds of the nurses and provide more career advancement for them in order to enhance the level of job satisfaction among the registered nurses.